Research on the framework of full-process condition monitoring and evaluation method for express logistics based on multi-information fusion and intelligent identification. Issue 1 (January 2020) - Ma, Luping; Zhang, Yuan; Du, Yanping; Huang, Lei
Abstract: This paper describes the background and significance of the whole process state monitoring of express logistics in the three aspects of environment, society and economy, then introduces the current status of the tracking and monitoring of logistics process at home and abroad, and proposes the method of full-process condition monitoring and evaluation method for express logistics based on multi-information fusion and intelligent identification, The content of the method mainly includes: collecting data based on various information collection methods such as sensors, extracting and identifying the characteristics of expressive behavior through the algorithm and quantitative evaluation of the whole process express logistics status.finally, Finally, the paper summarizes the whole system-based method of multi-information fusion and intelligent identification of the whole logistics process monitoring and evaluation, and explains the follow-up work direction and content.